Leveraging the broad powers of legislators to accelerate action to reduce road traffic casualties. Issue 2 (3rd April 2019) - Murphy, Evelyn
Abstract: This is an editorial highlighting the power that legislators have in improving global road safety and the failure of the road safety community in optimizing the existing capital of this resource. It argues that legislators must prioritize and adopt laws to improve road safety in their own countries and allocate resources for their enforcement. It also emphasizes the need for legislators to act through regional and global parliamentary bodies to accelerate the adoption and enforcement of laws on a broad scale and on a wide range of topics (such as funding, lead agencies, vehicle regulations), not only on regulating road user behaviour.